Ruling on women taking over the judiciary A comparative jurisprudence study (Journal of the College of Basic Education, 2022)
Praise be to God who made praise to Him without the need for Him to praise Him as a way of acknowledging His steadfastness and compassion and a reason for more of His mercy and the way for the seeker of His bounty. For every word of praise, even if it is bone.And I bear witness that there is no god but Allah, alone with no partner, a testimony of the sincerity of the heart and the utterance of the tongue with it is a hidden sincerity, that He is the Creator, the Creator, the Most Beautiful Names for Him, there is nothing like Him, since the thing was of His will and it was not similar to its component. And I bear witness that Muhammad is His servant and Messenger, and the acknowledgment of his prophethood is linked to the acknowledgment of his divinity.